The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/prep.201700137
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Particle Size on the Combustion of CL‐20/HTPB Propellants

Abstract: The effect of nitramine particle size on the combustion behavior of inert binder based propellants has been extensively studied for RDX and HMX, but not CL-20. Although materials such as RDX and HMX are useful for particular combustion applications, CL-20 has a greater potential to improve the oxygen balance and energy density of a propellant. The current work investigates the effect of CL-20 particle size on the combustion of CL-20/HTPB propellants down to submicrometer sizes. An influence of particle size on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Zhao Qin [24] studied the effects of magnesium (Mg), amorphous aluminum(am_Al), and magnesium‐boron composites on the agglomeration and combustion properties of propellants. The addition of some other additives, such as fluorine‐containing polymer coating [25], CL‐20 [26], Fe 2 O 3 [27], and Ta/PH‐Fe [28], also has a certain influence on the ignition, combustion, and agglomeration characteristics of the propellant. Environmental pressure is also an important factor affecting the particle size of agglomerates.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao Qin [24] studied the effects of magnesium (Mg), amorphous aluminum(am_Al), and magnesium‐boron composites on the agglomeration and combustion properties of propellants. The addition of some other additives, such as fluorine‐containing polymer coating [25], CL‐20 [26], Fe 2 O 3 [27], and Ta/PH‐Fe [28], also has a certain influence on the ignition, combustion, and agglomeration characteristics of the propellant. Environmental pressure is also an important factor affecting the particle size of agglomerates.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of CL-20 and RDX on basic properties of CMDB propellants were investigated, the major findings could be summarized as follows: 1) The calculations on energetic properties for CL-20/RDX-CMDB propellants showed that energetic properties of propellant with CL-20 were superior to of propellant with RDX. 2) The data on burning rate revealed that with the increase of RDX/CL-20 mass fraction in the propellants, the burning rates at low pressure (2-8 MPa) remained almost the same but differ observably at high pressure (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). With the increase of CL-20 mass fraction in the propellants, the burning rates of propellants could be enhanced significantly, but the burning rates of propellants containing RDX decreased.…”
Section: Resultsmentioning
confidence: 97%
“…In another study, the thermal decomposition behavior of CL-20-NEPE propellant and the interaction among the compo-nents had been studied by Li Ding et al [16]. Joseph Kalman et al [17] investigated the effect of CL-20 particle size on the combustion of CL-20/HTPB propellants down to submicrometer sizes, the burning rate and combustion mechanism were discussed in detail. A large number of papers have been concerned with the combustion and energetic properties of HTPB and NEPE propellants [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In order to produce a usable propellant formulation, it is necessary to control the burn rate of the propellant, to prevent unacceptable performance (too high or too low pressure) for the intended purpose of the device. The equation linking the burning rate parameters is shown in (1) v=B × p n (1) where: v -burning rate, p -pressure in the motor chambre, B -const. depending on grain temperature and n -pressure exponent.…”
Section: Theoretical Partmentioning
confidence: 99%
“…This means that replacing the charge in standard metal components implied the composition of aluminium-free composite rocket propellants, providing a range increase of up to 20% compared with double-base propellants, but with higher combustion temperatures. This is why one of the possible solutions to aforementioned problems (smoke and temperature) has led to research in the field of nitramine propellants and replacement of a part of the ammonium perchlorate with HMX, RDX or CL-20, as the most representative and commonly used compounds [1].…”
Section: Introductionmentioning
confidence: 99%